2003
DOI: 10.1111/j.1460-9568.2003.03070.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental enrichment during adolescence reverses the effects of prenatal stress on play behaviour and HPA axis reactivity in rats

Abstract: Prenatal stress (PS) can produce profound and long-lasting perturbations of individual adaptive capacities, which in turn can result in an increased proneness to behavioural disorders. Indeed, in PS rats there is evidence of impaired social play behaviour, disturbances in a variety of circadian rhythms, enhanced anxiety and increased hypothalamic-pituitary-adrenal (HPA) axis reactivity. This study was designed to experimentally investigate the degree of reversibility of PS-induced disturbances of social play a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
197
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(217 citation statements)
references
References 71 publications
17
197
1
2
Order By: Relevance
“…32,39 However, the majority of the studies concur that EE attenuates the hypothalamic-pituitary-adrenal response to acute stress 32,36 and is able to reverse the effect of past stressors on the hypothalamic-pituitary-adrenal reactivity. 37,38 In our study, EE decreased the basal and the stress-induced plasma corticosterone levels. However, although plasma corticosterone levels of SC mice returned to basal levels 90 min after stress initiation, the EE mice plasma corticosterone remained significantly elevated.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…32,39 However, the majority of the studies concur that EE attenuates the hypothalamic-pituitary-adrenal response to acute stress 32,36 and is able to reverse the effect of past stressors on the hypothalamic-pituitary-adrenal reactivity. 37,38 In our study, EE decreased the basal and the stress-induced plasma corticosterone levels. However, although plasma corticosterone levels of SC mice returned to basal levels 90 min after stress initiation, the EE mice plasma corticosterone remained significantly elevated.…”
Section: Discussionmentioning
confidence: 77%
“…To date, no consensus on the effect of EE on resting plasma corticosterone levels is available. Although some studies have reported that EE decreased basal corticosterone levels, 35 others have reported no difference [36][37][38] or an increase in basal corticosterone levels. 32,39 However, the majority of the studies concur that EE attenuates the hypothalamic-pituitary-adrenal response to acute stress 32,36 and is able to reverse the effect of past stressors on the hypothalamic-pituitary-adrenal reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the effects exerted by environmental enrichment on social behaviors in animals have been poorly documented. To our knowledge, there are only two studies that have so far evaluated this issue and their results are inconsistent (Renner and Rosenzweig, 1986;Morley-Fletcher et al, 2003). In elucidating the attenuating effects of environmental enrichment in VPA rats, the known effects of enrichment on neurogenesis (Kemperman et al, 1997;Nilsson et al, 1999), neurotrophin gene expression (Torasdotter et al, 1996(Torasdotter et al, , 1998Young et al, 1999;Olsson et al, 1994;Ickes et al, 2000), and anatomical features (Diamond et al, 1964;Diamond, 1967;Rampon et al, 2000;Floeter and Greenough, 1979) should also be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…This pioneering observation generated a large number of studies, which have shown significant differences in animals' behavior associated with enriched living conditions. Environmental enrichment in rats leads to better performance in various learning tasks (eg Greenough et al, 1972;Mohammed et al, 1990;Nilsson et al, 1999;Rampon et al, 2000), enhanced social play behavior (Morley-Fletcher et al, 2003), increased exploration, lower anxiety, and ameliorated plasma corticosterone response to stress (Levine, 1962(Levine, , 1967. Experiments have shown that improvements in behavioral performances were accompanied with changes in various neurochemical and anatomical features in rat brains.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, enriched environment (EE) and cross fostering both are able to offset prenatal stress effects and normalize HPA axis function and affective states [82,97,98]. Notably, interactions by multiple treatments may cancel or enhance each other's benefit [99][100][101].…”
Section: Transgenerational Programming Of Stress Resiliencementioning
confidence: 99%